The Globalisation of Inflation: The Growing Importance of Global Value Chains - Raphael A. Auer; Claudio Borio; Andrew Filardo (Center for Economic Studies and ifo Institute (CESifo), 2017)
Greater international economic interconnectedness over recent decades has been changing inflation dynamics. This paper presents evidence that the expansion of global value chains (GVCs), ie cross-border trade in intermediate goods and services, is an important channel through which global economic slack influences domestic inflation. In particular, we document the extent to which the growth in GVCs explains the established empirical correlation between global economic slack and national inflation rates, both across countries and over time. Accounting for the role of GVCs, we also find that the conventional trade-based measures of openness used in previous studies are poor proxies for this transmission channel. The results support the hypothesis that as GVCs expand, direct and indirect competition among economies increases, making domestic inflation more sensitive to the global output gap. This can affect the trade-offs that central banks face when managing inflation.
Keywords: E31; E52; E58; F02; F41; F42; F14; F62; 330; globalization; inflation; Phillips curve; monetary policy; global value chain; production structure; international inflation synchronisation; input-output linkages; supply chain